Architecture of Topic - Egerland, Verner; Molnár, Valéria; Winkler, Susanne (Studies in Generative Grammar [SGG], 2019)
This volume contains innovative papers that target the linguistic status of topic at the interface between grammar and discourse. The purpose of the volume is to discuss the universal properties of topics and, at the same time, to document the range of discourse-semantic and grammatical variation within this phenomenon in European languages. The volume is structured accordingly: (i) theoretical foundations of topicality in grammar and discourse; (ii) discourse-semantic correlates of topicality; (iii) variation in the grammatical (external and internal) encoding of topicality; (iv) topics from the diachronic perspective. The articles take different perspectives, including contrastive studies of modern languages, studies on diachronic development, and typological generalizations. They also take into consideration various types of empirical data - introspective data, semi-spontaneously produced data, experimental data and language corpora. The articles in this volume show that the concept of topic is necessary for the description and explanation of a number of discourse-semantic phenomena. They present a state of the art account of the architecture of topic while making recent research on the phenomenon accessible to a wider readership